Highly adhesive and disposable inorganic barrier films: made from 2D silicate nanosheets and water. Issue 4 (6th January 2022) - Eguchi, Miharu; Konarova, Muxina; L. Torad, Nagy; Chang, Te-An; Kang, Dun-Yen; Shapter, Joe; Yamauchi, Yusuke
Abstract : A gas barrier film with moderate permeance due to capillary flow and high adhesion was made from only water and layered aluminosilicates. Interestingly, gas permeability decreased with increasing humidity. This film preserved the freshness of apples. Abstract : A gas barrier film with moderate permeance due to capillary flow and high adhesion was made from only water and layered aluminosilicates. The surface adsorbed water acts as a polar binder between the layers of aluminosilicates which enhances gas barrier efficiency, especially toward less polar gases. Oxygen permeability was 4.91 × 10 −16 mol m m −2 s −1 Pa −1 (23 °C, 60% relative humidity (RH), permeance: 4.31 × 10 −12 mol m −2 s −1 Pa −1 ), which is 1/26th that of Kraft paper (at 25 °C, 65% RH) and 146 times that of polyvinylidene chloride films. This film with moderate gas permeability is suitable for the preservation of fresh produce requiring low level respiration after harvest. The film applied to the surface of apples preserved their freshness, presumably by blocking oxygen transfer and microorganisms. Furthermore, the high adhesion of this film is more expedient for blocking gases generated from produce because the film excludes gaps between the film and the produce, which is difficult for usual cling wraps. This film can also be used for cultivating produce instead of conventional pesticides because it reduces the emission of aromatic volatiles that attract pests. This sustainable film whose component is the same as the main component of soil has the potential to reduce food loss. In addition, the film from another smectite with larger lateral size was revealed to have lower gas permeability due to diffusion and not capillary flow.